Pathogenic Bacterial Communities of Dust in a Coal Mine - Xue, Sheng; Liu, Xiaozhou; Li, Yang; Liu, Bingjun; Tu, Qingyi; Li, Cheng (Frontiers in Environmental Science, 2022)
Coal mine dust is an important factor leading to occupational diseases of mine workers, however, it remains poorly understood about the non-viral pathogens in coal mine dust. In this study, bacterial communities in total dust and respirable dust from different laneways in Hongliulin coal mine (Shaanxi, China) were analyzed by PacBio high-throughput sequencing. The results showed no significant differences in the number, diversity and structure of bacterial communities in different laneways. Gammaproteobacteria, Alphaproteobacteria and Betaproteobacteria were the numerically dominant groups in dust samples which accounted for 72.5 % of the total sequences. Among them, a total of 7 known bacterial pathogens species including Aeromonas hydrophila, Burkholderia cenocepacia, Klebsiella pneumoniae, Proteus vulgaris, Serratia marcescens, Staphylococcus epidermidis and Staphylococcus saccharolyticus and 2 bacterial genera (Actinomyces and Peptostreptococcus) with extensive pathogenicity were detected in the respirable dust samples. And linear discriminant analysis (LDA) indicated that prominent pathogens were detected in the respirable dust for the return laneway and the digging tunnel, such as K. pneumoniae and S. saccharolyticus in return laneway and B. cenocepacia in the digging tunnel. In parallel, PICRUST2 was performed to predict the functions in dust, and the human diseases count accounted for 4.31 % of the total predictive function. In addition, the predictive count of human diseases in the respirable dust was closely related to bacterial diversity and structure. In summary, this study complemented the information of pathogenic bacteria in dust, especially in respirable dust, and suggested that non-viral pathogens should be considered in the process of mine dust prevention and control.